2018
DOI: 10.1172/jci97072
|View full text |Cite
|
Sign up to set email alerts
|

Hijacking a key chromatin modulator creates epigenetic vulnerability for MYC-driven cancer

Abstract: While the genomic binding of MYC protein correlates with active epigenetic marks on chromatin, it remains largely unclear how major epigenetic mechanisms functionally impact the tumorigenic potential of MYC. Here, we show that, compared with the catalytic subunits, the core subunits, including DPY30, of the major H3K4 methyltransferase complexes were frequently amplified in human cancers and selectively upregulated in Burkitt lymphoma. We show that DPY30 promoted the expression of endogenous MYC and was also f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 65 publications
2
30
0
Order By: Relevance
“…Sequence‐specific transcription factors (TFs) contribute to the recruitment of co‐activators and/or components of the basal transcription machinery to their cognate binding elements in the genome: this is a reciprocal relationship, however, as many TFs depend on the same interactions to access target regulatory regions in the genome, prior to sequence‐specific DNA binding . MYC, in particular, requires an active, open chromatin conformation to access its target DNA sequences, which is facilitated by its interaction with proteins such as WDR5, DPY30 (two components of the H3K4 methyltransferase complex SET1/MLL), BPTF (a component of the NURF chromatin remodeling complex) and possibly others among numerous interacting co‐factors . This initial step in genome recognition might be susceptible to pharmacological intervention, as exemplified by targeting of the MYCN‐WDR5 interaction in neuroblastoma cells, with a consequent reduction in MYCN‐dependent transcription and cell growth .…”
Section: Targeting Myc Addictionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sequence‐specific transcription factors (TFs) contribute to the recruitment of co‐activators and/or components of the basal transcription machinery to their cognate binding elements in the genome: this is a reciprocal relationship, however, as many TFs depend on the same interactions to access target regulatory regions in the genome, prior to sequence‐specific DNA binding . MYC, in particular, requires an active, open chromatin conformation to access its target DNA sequences, which is facilitated by its interaction with proteins such as WDR5, DPY30 (two components of the H3K4 methyltransferase complex SET1/MLL), BPTF (a component of the NURF chromatin remodeling complex) and possibly others among numerous interacting co‐factors . This initial step in genome recognition might be susceptible to pharmacological intervention, as exemplified by targeting of the MYCN‐WDR5 interaction in neuroblastoma cells, with a consequent reduction in MYCN‐dependent transcription and cell growth .…”
Section: Targeting Myc Addictionmentioning
confidence: 99%
“…This initial step in genome recognition might be susceptible to pharmacological intervention, as exemplified by targeting of the MYCN‐WDR5 interaction in neuroblastoma cells, with a consequent reduction in MYCN‐dependent transcription and cell growth . DPY30 might also be promising target in this regard, as its gene was frequently amplified in human cancer, was upregulated in BL, and was limiting for lymphomagenesis in Eμ‐ myc mice …”
Section: Targeting Myc Addictionmentioning
confidence: 99%
“…We have shown that DPY30 depletion impaired c-MYC (MYC) expression and growth of several MLL-rearranged leukemias without affecting K562 leukemia cells driven by different mechanisms (17). We have also found that the expression of the core subunits including DPY30 was significantly upregulated in primary MYCtranslocated Burkitt's lymphoma samples comparing to other lymphoma subtypes (20). Deleting one Dpy30 allele in mice significantly delayed the Eµ-MYC-driven lymphomagenesis, with virtually no effect on normal mouse physiology.…”
Section: Introductionmentioning
confidence: 97%
“…An important role of DPY30 in tumorigenesis is also increasingly evident. Genes encoding the SET1/MLL complex core subunits including DPY30 are frequently amplified across a wide variety of human cancers (20). DPY30 is overexpressed in gastric cancer cells and also positively regulates the proliferation and motility of these cells (21).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation